PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM PAI - Suyyirah; Maimun; Maysurah (As-Sulthan Journal of Education, 2025)
Islamic Religious Education (IRE) is an integral component of the national education system, aiming to shape individuals who are faithful, devout, and morally upright. In the context of a rapidly evolving modern society, the development of the IRE curriculum must be carried out in a planned and systematic manner, based on strong principles to address contemporary challenges without losing its Islamic identity. The IRE curriculum serves not only as a medium for conveying religious knowledge but also as a vehicle for character and spiritual development of students. The development of the IRE curriculum must be grounded in fundamental principles such as relevance to the needs of students and society, flexibility in the face of change, continuity across educational levels, practical efficiency, and the integration of Islamic values into all aspects of learning. These principles are crucial in ensuring that the IRE curriculum produces a generation of Muslims who not only understand religion theoretically but are also capable of applying it in real life. Therefore, understanding the core principles in developing the IRE curriculum is essential for educators, curriculum designers, and educational stakeholders, to ensure that the objectives of religious education are achieved optimally in nurturing the nation’s character and morality.